Leadership practices and teacher satisfaction: the critical role of trust and professional development in mid-career stages - Balan, Adriana; Jamaluddin, Rahimah (Human Resources Management Academic Research Society (HRMARS), 2024)
Collaborative leadership, characterized by shared decision-making and teamwork, is closely linked to enhanced teacher satisfaction, as it fosters a supportive and inclusive work environment. However, there is a scarcity of empirical research specifically investigating the impact of principals' collaborative leadership on teacher satisfaction in the Malaysian context. This study adopts a quantitative approach using a survey method and applies multilinear regression analysis to explore the impact of different dimensions of collaborative leadership on teacher satisfaction. The population consists of 2,157 teachers from 38 primary and secondary schools, with a sample size of 331 teachers selected through simple random sampling. The findings indicate that collaborative leadership significantly impacts teacher satisfaction. Key dimensions such as developing the people around, building trust, sharing power and influence, and having a clear vision in leadership were found to enhance teacher satisfaction, accounting for 95.6% of the variance in satisfaction levels. Developing the people around was identified as the most significant predictor of teacher satisfaction, highlighting the importance of professional development and support. Conversely, environmental factors did not significantly influence satisfaction. These results suggest that principals who foster a collaborative environment, build trust, share power, and articulate a clear vision can substantially improve teacher satisfaction. The findings also suggest that at mid-career stages, teachers are likely to seek opportunities for professional development that allow them to expand their skills and take on new challenges. The implications for educational policy and practice include emphasizing collaborative leadership in training programs for school leaders to foster a supportive and engaging work environment for teachers.